Aggregation when Markets do not Clear - Leif Andreassen (Statistics Norway, Research Department, 1995)
This paper presents a method for aggregation across markets in a Non-Walrasian model, focusing mainly on labor markets. The method utilizes a probabilistic approach based on aggregating across virtual price functions instead of demand functions or budget shares as is normally done. By assuming log-linear virtual price functions and using the GEV distribution, it is possible to identify most of the micro structure of an economy in disequilibrium from observed aggregate variables. The paper discusses different possible indicators of disequilibrium in the labor market and presents some illustrative estimation results.
Keywords: E1; C5; D5; 330; Aggregation; disequilibrium; non-Walrasian models.